Third-party remanufacturing mode selection for a capital-constrained closed-loop supply chain under financing portfolio. (July 2021) - Zhang, Yongming; Chen, Weida; Li, Qianru
Highlights: Capital constraint is introduced into third-party remanufacturing mode selection. Financing portfolio strategy of trade credit and bank loan is adopted. Default risk of financing behavior is considered. Impacts of capital constraint and financing portfolio on third-party remanufacturing mode selection are analyzed. Abstract: Remanufacturing, especially third-party remanufacturing, has become an important option for original equipment manufacturers (OEMs) to effectively balance the economic benefits and environmental impacts of their operations. Further, capital constraint and financing behavior have critical impact on the operations of OEMs, especially small- and medium-sized OEMs. Hence, we aim to explore how the OEM's capital constraint and financing behavior will affect its selection preference regarding the two sub-modes of third-party remanufacturing: outsourcing and authorization. To this end, we consider a dyadic closed-loop supply chain consisting of a leading third-party remanufacturer (TPR) and a capital-constrained OEM. Taking the case of no capital constraint as benchmark, the choice preference of remanfuacturing modes between outsourcing and authorization is investigated under the case of capital constraint and financing portfolio (including trade credit and bank loan). The findings are as follows. Compared with the benchmark case of no capital constraint, under the financing portfolio, the OEM's choice preference shifts from outsourcing mode to authorization mode, while the TPR's choice preference shifts from authorization mode to outsourcing mode. From the perspective of the whole supply chain (SC), the authorization mode would always be conducive to promoting the total profit of the SC when the OEM is capital-unconstrained. By contrast, in the case of financing portfolio, outsourcing mode would be more preferred by the SC except when remanufacturing is much profitable. The above suggests that the TPR and OEM should change their selection preferences when the OEM is severely capital-constrained. Moreover, a contract should be signed between the TPR and OEM to handle their conflicts in selection preference, and who plays an active role in coordinating the SC depends on the profitability of remanufacturing.